2021
DOI: 10.1111/jcv2.12005
|View full text |Cite
|
Sign up to set email alerts
|

Understanding why the COVID‐19 pandemic‐related lockdown increases mental health difficulties in vulnerable young children

Abstract: Background:The mental health consequences of school closure, social isolation, increased financial and emotional stress, and greater exposure to family conflicts are likely to be pronounced for primary school children who are known to be vulnerable. Data from prior to the pandemic are needed to provide robust assessments of the impact of COVID-19 on vulnerable children. Method:The present study capitalises on an ongoing study of primary school children (4-8 years) identified as 'at-risk' for mental health prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 31 publications
7
81
3
4
Order By: Relevance
“…The change was most prominent in internalizing problems with increased generalized anxiety, panic and somatic symptoms, and school anxiety and decreased social and separation anxiety. There was no increase in externalizing problems in this sample which had high levels of externalizing problems at baseline [36].…”
Section: General Population Clinical and At-risk Samplesmentioning
confidence: 49%
See 2 more Smart Citations
“…The change was most prominent in internalizing problems with increased generalized anxiety, panic and somatic symptoms, and school anxiety and decreased social and separation anxiety. There was no increase in externalizing problems in this sample which had high levels of externalizing problems at baseline [36].…”
Section: General Population Clinical and At-risk Samplesmentioning
confidence: 49%
“…As noted earlier, some types of anxiety (e.g., social anxiety, separation anxiety, performance anxiety) may have decreased in the context of home confinement because the usual pressures associated with school and social interactions were lessened. In the study of Welsh children by Adegboye and colleagues [36], generalized anxiety, panic and somatic symptoms, and school anxiety increased while social and separation anxiety decreased. Thus, children with social anxiety, social phobia, performance anxiety, and/or agoraphobia may experience temporary symptom reduction with school closure, physical distancing, and a decrease in daily stresses.…”
Section: Improved Outcomesmentioning
confidence: 94%
See 1 more Smart Citation
“…Further investigations could account for previous/existing mental health problems in children and parents, as it was shown that especially vulnerable groups suffer more under the pandemic and that parents mental health during the pandemic was related to the child-SDQ-scores. 30 This could shed light on the intended hypothesis, that supporting parent's mental health might also be helpful for protecting children's mental health. Further analyses should also take data for living-situations and family compositions into account.…”
Section: Discussionmentioning
confidence: 99%
“…5 A study looking at primary school children found that financial strain within the family was linked to increased mental health difficulties in children because of an increase in parental anxiety and depression. 6…”
Section: Why Have Referrals To Camhs Changed?mentioning
confidence: 99%